Effects of process parameter on performance measures in electrical discharge machining using copper and brass electrodes. (2021) - Selvarajan, L.; Senthil kumar, N.; Raja, R.; Sasikumar, R.; Muralidharan, V.
Abstract: In the study of modern-day technology, it's performance and parameters are evaluated using the EDM process in the drilling of stainless steel 316 material. SS316 material is widely used in many industrial applications such as heat transfer process and chemical tank. This test involves testing more material removal rate, improving the material hardness, reducing the electrode wear rate and machining time. The experiment is based on Taguchi L18 orthogonal array with 6 levels and 6 parameters like current, dielectric pressure, electrode shape, spark gap, polarity, pulse on and off time. Comparison of copper and brass electrodes in this experiment research is being conducted on how copper electrodes behave differently and exhibit better mechanical performance than brass electrodes. Brass electrode, with its high electrical resistance, low melting point and low thermal conductivity, copper has better performance than brass electrode and the different experimental levels and conditions are investigated.